Letteratura nella cattedrale. Il sorriso di Becket (Doctor Virtualis, 2021)
In the Middle Ages, so often depicted in literature as a great adventure novel, a very special place belongs to the story of Thomas Becket, firstly chancellor of King Henry II and later Bishop of Canterbury, murdered in his cathedral in 1170. This episode presents the fundamental motifs of every epic and tragic tale. Inspired by this conviction, this article examines some of the most significant literary works that have described the conflict between Becket and his king from different points of view: some of the medieval hagiographies, Alfred Tennyson, Conrad Ferdinand Meyer in the 19th century, and – in the 20th – Thomas Stearns Eliot, Christopher Fry and Jean Anouilh.It is very difficult to get a precise idea of the real Thomas Becket, while the great metaphor proposed by John of Salisbury, his close collaborator, of life and history as a theatrical representation in which only the roles that men are called to play are of decisive importance, seems to have been realized.